Volume 1: Codes, Standards and Regulations; Design and Constructions; Environmental; GIS/Database Development; Innovative Proje 2000
DOI: 10.1115/ipc2000-125
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Microalloyed Linepipe Steels

Abstract: The aim of this study was to characterize the microstructure of microalloyed linepipe steels. The steels investigated were X70 (0.04 wt% C - 0.02 wt% Ti - 0.07 wt% Nb) and X80 (0.04 wt% C - 0.025 wt% Ti - 0.09 wt% Nb) steels, where the numbers refer to their specified minimum yield strength (SMYS) in ksi. This class of steels has the advantage of high strength and good toughness combined with minimal wall thickness (15.5 mm for X70 steel). These attributes result in considerable cost savings when installation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The microstructure observed by optical microscope was characterized by irregular ferrite. Further observation by TEM revealed that, acicular-like microstructure was actually composed of the subgrain within the acicular ferrite structure, and was constituted with nearly parallel lathing ferrites in which orientation margin of adjacent interfaces was small angle [8,9]. The effective grain size of acicular ferrite was actually the diameter of lathing bundle in it, the corresponding value was no more than 2-3 lm.…”
Section: Analysis and Discussionmentioning
confidence: 98%
“…The microstructure observed by optical microscope was characterized by irregular ferrite. Further observation by TEM revealed that, acicular-like microstructure was actually composed of the subgrain within the acicular ferrite structure, and was constituted with nearly parallel lathing ferrites in which orientation margin of adjacent interfaces was small angle [8,9]. The effective grain size of acicular ferrite was actually the diameter of lathing bundle in it, the corresponding value was no more than 2-3 lm.…”
Section: Analysis and Discussionmentioning
confidence: 98%
“…Alternatively, XRD broadening may arise from a polycrystalline precipitate structure (i.e., the domain size is a measure of the grain size within the precipitate and not the total precipitate size). However, selected area diffraction (SAD) analysis of the relatively large microalloyed steel precipitates [1] indicates the precipitates are single crystals; as such, the domain and precipitate size are equivalent.…”
Section: Size Of Precipitates >90 Nmmentioning
confidence: 99%
“…The characterization of precipitates in microalloyed steels can be undertaken using a number of analytical techniques, including optical microscopy [1,2], scanning electron microscopy (SEM) [3][4][5][6], transmission electron microscopy (TEM) [2,3,7,8], energy dispersive X-ray (EDX) analysis [2,3,8,9], and small angle neutron scattering (SANS) [10]. Each technique has its own advantages (and disadvantages) in terms of quantifying the number density, volume or weight fraction, composition and/or size of the precipitates.…”
Section: Introductionmentioning
confidence: 99%
“…Development of construction in transmission pipeline for oil and gas evolves the requirement of microalloyed steels with higher strength and lower price. Increasing of steel grade will reduce costs of pipe production and implementing action [2]. API X70 steel is categorized in the high strength microalloyed steels and is used as the main steel in production of the transmission pipelines of oil and gas, due to the mechanical strength.…”
Section: Introductionmentioning
confidence: 99%